Imersão estrutural, imersão relacional e competência de rede como impulsionadores da qualidade dos serviços das unidades básicas de saúde - Gabriel, Mikaelli Orlande (2014)
This study aimed, from mapping the network of relationships among the 29 basic health units in the city of Victoria, to investigate the relationship between network competence and relational and structural immersions with the quality of service provided b